(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This scientific article provides a brief understanding of the original source on the laws and regulations of the establishment of a kingdom, which were first formulated in the Middle Ages. For more information, please refer to my specially prepared dissertation: "Al-Mawardi’s "al-Ahkom al-sultaniyya" - an important source on the history of state governance in the Muslim East (11th century)". It provides a detailed description of the life, political and scientific activities of Abulhasan Mawardi. It provides sufficient research materials on the fact that he founded the science of political jurisprudence in his time, was recognized by his students and scholars, was used in the establishment of the kingdom in various regions over the centuries, and translations of the work into Arabic, French, English, Flemish, Persian, Urdu, Malay, Turkish, Uzbek, and manuscript copies.